Probing key informants' views of health equity within the World Health Organization's Urban HEART initiative - Michelle Amri; Patricia O'Campo; Theresa Enright; Arjumand Siddiqi; Erica Di Ruggiero; Jesse Boardman Bump (BMC, 2022)
Abstract To date, no studies have assessed how those involved in the World Health Organization's (WHO) work understand the concept of health equity. To fill the gap, this research poses the question, "how do Urban Health Equity Assessment and Response Tool (Urban HEART) key informants understand the concept of health equity?", with Urban HEART being selected given the focus on health equity. To answer this question, this study undertakes synchronous electronic interviews with key informants to assess how they understand health equity within the context of Urban HEART. Key findings demonstrate that: (i) equity is seen as a core value and inequities were understood to be avoidable, systematic, unnecessary, and unfair; (ii) there was a questionable acceptance of need to act, given that political sensitivity arose around acknowledging inequities as "unnecessary"; (iii) despite this broader understanding of the key aspects of health inequity, the concept of health equity was seen as vague; (iv) the recognized vagueness inherent in the concept of health equity may be due to various factors including country differences; (v) how the terms "health inequity" and "health inequality" were used varied drastically; and (vi) when speaking about equity, a wide range of aspects emerged. Moving forward, it would be important to establish a shared understanding across key terms and seek clarification, prior to any global health initiatives, whether explicitly focused on health equity or not.